The Spectropolitics of Romantic Infidelism: Cruikshank, Paine, and The Age of Reason - Haywood, Ian (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThe aim of this article is to take a fresh look at Romanticism’s arch ‘infidel’, Thomas Paine. My approach is to place his key work The Age of Reason (1795) in the context of what Derrida in Spectres of Marx calls ‘spectropolitics’. Derrida coins this term to describe the way in which ‘effectivity phantamolizes itself,’ and I want to use Derrida’s insight to explore the specifically visual dimension of Paine’s ‘phantomal’ image. I will show that there are three components to the spectropolitical transformation of Paine: his demonization in the 1790s as the diabolical seducer of the common reader; his ‘resuscitation’ in the post-war period by Richard Carlile and other ‘apostles’; and the ironic conjunction between this contested ‘apotheosis’ of Paine and his Deistical debunking of Christian revelation as vulgar spectacle. I focus my discussion around George Cruikshank’s print The Age of Reason (1819) in order to show that caricature was a major spectropolitical force in the Romantic period and the apposite cultural medium for negatively ‘phantamolizing’ Paine, though this tactic always ran the risk of further enhancing his ‘cult’ status in radical martyrology. The larger critical aim of the article is to open up a new area in Romantic studies: to redefine Romanticism in terms of ‘spectropolitics’ gives popular visual media such as caricature a primary rather than secondary critical function, and it allows us to rethink and revalue the ‘phantasmagoric’ transformation of Romantic politics and culture.